Creating Biodiesel from Used Coffee Grounds - Eaves, Carly M. (My University, 2020)
Many people in today’s world rely heavily on fossil fuels, primarily coal and oil, to provide their energy or power. However, scientists have since discovered that fossil fuels release carbon dioxide, a greenhouse gas that traps heat in the atmosphere, when they are burned. This has been a major cause of climate change and global warming. Therefore, the search for alternative energy sources has become more critical now than ever. One possible source of alternative energy is biodiesel. Biodiesel is a vegetable oil or animal fat-based diesel that is made up of long chain alkyl esters. It is typically made by reacting lipids with alcohol, producing fatty acid esters. The goal of the researchers in this experiment was to find the most optimal way to convert coffee oil from used coffee grounds to biodiesel with the highest yield using transesterification. Through a series of three trials, the optimum conditions for the reaction were discovered to be 40%v MeOH and 1.5 wt% KOH (catalyst).